Similarity functions of acoustic patterns as indices of the objective quality evaluation of speech transmission - Czesław BASZTURA (Archives of Acoustics)
This study is concerned with a new, objective quality evaluation of speech transmission through telephone lines. The conception of the studies is based on the assumption of equivalency between the results of subjective and objective measurements. A special purpose of the study was to investigate the efficiency of the similarity function of the acoustic patterns of signals as an indice of the objective quality evaluation of speech transmission. Altogether, the usefulness of 8 functions of similarity were investigated, such as the Hamming, Euclid, Minkowski, Tanimoto, Chebyshev, Camberra distances, y-square and directional cosine. The obtained preliminary results indicate for some similarity functions good agreement with subjective results obtained by the subjective method.